Transformaç\~ao digital para cidades inteligentes, resilientes e sustentáveis: Uma vis\~ao centrada no cidad\~ao - Luis Claudio Kubota (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This article deals with three major issues. The first is digital transformation in the context of a smart city seeking continuous action to leverage technologies to improve the design and delivery of services. The second is resilience. The third is sustainable development, defined as one that meets current needs without compromising the ability of future generations to meet their own needs. The study has several goals. The first is to survey the international and national analytical framework on smart and resilient cities. At the international level, there is a focus on two analytical frameworks of the United Nations - united by smart and sustainable cities (U4SSC) and the Sendai Protocol, which present quite comprehensive views on their respective themes. In addition, it seeks to present digital government initiatives that are subject to adoption by both states and municipalities and illustrate the importance of the citizen-centered view in its design and implementation.
Keywords: H77; H84; L86; L9; O19; Q9; Q54; 330; smart cities; sustainability; resilience